Barley = 맥 - Kim, Namcheon (바이링궐 에디션 한국 대표 소설, 2015)
In "Barley", two intellectuals, Sihyǒng and Kwanhyǒg, represent only one aspect of mourning for their past ideology. The possibility of mourning that combines introjection and incorporation is represented by Mugyǒng, a person who has been living normal working life. In other words, Mugyǒng, who has nothing to do with mourning, represents the possibility of a new life. Mugyǒng, who did not begin with an ideology from the outset, resolves to live a sincere life based on "active resignation." We witness in this character traces of the hearbreakingly difficult struggle that Kim Namch'on went through while trying to see even a little light in the darkness of the late-colonial period."